Performance Evaluation of a Chiller System for Nutrient Solutions Temperature Control in Lowland Tropical Hydroponic Strawberry Cultivation - Icha Fatwasauri; Rhesti Nurlina Suhanto; Friska Afadillah (Jurnal Keteknikan Pertanian, 2026)
Hydroponic strawberry cultivation in tropical lowland regions is constrained by elevated ambient temperatures that increase Nutrient Solution Temperature (NST) beyond the optimal Root-Zone Temperature (RZT) range required for plant growth, leading to thermal stress, reduced nutrient uptake, and yield losses. This study aimed to design and evaluate the performance of a chiller-based cooling system integrated into a recirculating hydroponic setup to maintain the NST within the optimal range of 17–20°C for strawberry cultivation. A laboratory-scale prototype employing a vapor-compression refrigeration system using the R32 refrigerant was developed and tested under tropical conditions. The thermal performance of the system was assessed through cooling load calculations, thermodynamic analysis, and real-time monitoring of temperature, pressure, electrical parameters, and hydraulic conditions, whereas plant growth responses were observed qualitatively. The results demonstrate that the proposed system effectively reduced NST from elevated initial conditions to the target range within 18 minutes and maintained temperature stability using an on–off control strategy. The system achieved a stable actual Coefficient of Performance (COP) of approximately 4.02 with an overall efficiency of approximately 56%, indicating reliable operation under practical conditions. Root-zone temperature control significantly enhanced vegetative growth, leaf quality, and fruit uniformity compared with plants grown without cooling. The findings confirmed that direct nutrient solution cooling using a vapor-compression chiller is a viable and scalable engineering solution for hydroponic strawberry cultivation in tropical lowlands. This study contributes empirical performance data to the limited literature on chiller-integrated hydroponic systems and provides a practical foundation for extending high-value strawberry production into hot climates, while supporting sustainable and controlled agricultural practices.